2008
DOI: 10.1111/j.1365-2672.2007.03639.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen profiles of the fish pathogen Moritella viscosa and protection in fish

Abstract: Aims:  Moritella viscosa is a Gram‐negative bacterium that causes winter ulcer disease in salmonid fish cultured in sea water below 8°C. The aim of this study was to study the antigen profiles of these bacteria and to reveal the protection which the antigens induce in fish. Methods and Results:  Lipooligosaccharides (LOS) and an approximately 17–19 kDa outer membrane antigen were shown to be the major specific antigens of M. viscosa. The size of the wall antigen differed between strain groups and even between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
1
28
1
1
Order By: Relevance
“…A degree of geographically based amplified fragment length polymorphism (AFLP) clustering within Moritella viscosa isolates has been demonstrated and the existence of 4 different serotypes was recently shown (Heidarsdóttir et al 2008). However, until the present study the Norwegian M. viscosa population had been considered relatively homogeneous, an assumption probably based on lack of evidence to the contrary, rather than direct evidence of homogeneity.…”
Section: Introductioncontrasting
confidence: 39%
See 2 more Smart Citations
“…A degree of geographically based amplified fragment length polymorphism (AFLP) clustering within Moritella viscosa isolates has been demonstrated and the existence of 4 different serotypes was recently shown (Heidarsdóttir et al 2008). However, until the present study the Norwegian M. viscosa population had been considered relatively homogeneous, an assumption probably based on lack of evidence to the contrary, rather than direct evidence of homogeneity.…”
Section: Introductioncontrasting
confidence: 39%
“…Isolates from Atlantic salmon in Norway must therefore account for the overwhelming majority of clinical M. viscosa isolates on a worldwide basis. Despite the antigenic differences identified during the present study and by Heidarsdóttir et al (2008), crossprotection has been reported between Icelandic (presumed variant) and Norwegian (typical) strains (Greger & Goodrich 1999). The previous assumption of homogeneity may therefore not have been as significant in relation to protection of vaccinated stocks as it otherwise might have been.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Jellyfish Cyanea lamarckii provides the natural habitat for Moritella viscosa, which causes necrotic ''winter ulcer'' in salmons (Lunder et al 2000;Heidarsdottir et al 2008), additionally Arcobacter butzleri, a human pathogen species (Carbone et al 2003;Gugliandolo et al 2007), and finally members of group #4 (see the previous paragraph). The Lions mane jellyfish C. capillata carries the haemolytic species Shewanella waksmanii, a member of group #3 (Ivanova et al 2003), and pathogenic endobionts of the already described Photobacterium profundum and the putatively pathogenic species of groups #1 and #4 (see the previous paragraph).…”
Section: Pathogenic Activities Of Bacterial Endobiontsmentioning
confidence: 99%
“…Individuals of Cyanea lamarckii, Cyanea capillata, Tubularia indivisa and Sagartia elegans were collected by divers during research cruises (June/July 2005-2008) from waters around the Orkney Islands. Tips of fresh tentacles were clipped off and subjected to washing procedures and CTAB treatment ) in order to remove potentially contaminating epibiotic bacteria.…”
Section: Samples and Preparationmentioning
confidence: 99%